Self-Esteem and its Relationship with the Age, Gender and academic Achievement among the students of the south Iraq Colleges of Nursing - Raja, Hayder; Sajit, Kareem (Iraqi National Journal of Nursing Specialties, 2018)
Abstract Objectives: this study aims to: (1). Assess self-esteem level and academic achievement for students of nursing colleges in southern Iraq. (2). Determine the relationship between levels of self-esteem and academic achievement of the student in the first semester. (3). Identify differences of self-esteem with gender and different age groups. Methodology: a sample of (426 students) was purposively selected then collected by using a questionnaire which consisted of: I- Sociodemographic characteristics for assessing some important aspects of students, II- Rosenberg’s Self-Esteem Scale (RSES) III- Iraq Grading Scale for assessing student achievement. Finally statistical analysis (SPSS) for data processing. Results: study results showed that there was a very strong positive relationship between self-esteem and academic achievement. While there were no associations to neither gender differences nor different age groups. Recommendations: It is recommended for teachers to promote students’ self-esteem level through feeding-them-back and positive rewards, to feel more confident and promote the sense of self-competence Also, it is recommended to repeat this study –in future– including the whole nursing colleges in Iraq, for more comprehensive and generalized results